Europe enlarged a handbook of education, labour and welfare regimes in central and eastern Europe - Kogan, Irena 1973-; Gebel, Michael 1979-; Noelke, Clemens 1980- (Policy Press, 2008)
This important reference work describes the educational systems, labour markets and welfare production regimes in the ten new Central and Eastern Europe countries
Keywords: European Union; Public welfare / Europe, Central; Public welfare / Europe, Eastern; Labor market / Europe, Central; Labor market / Europe, Eastern; Education / Europe, Central; Education / Europe, Eastern; Arbeitsmarkt; Sozialer Wandel; Bildungssystem; Osteuropa; Aufsatzsammlung